INTERNALISASI NILAI-NILAI KEAGAMAAN MELALUI BUDAYA JUM’AT BERIMAN UPAYA PENGUATAN KARAKTER SMK JALALUDDIN WONOSOBO - Inayati, Fela Fauziyah; Khuriyah, K (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Internalizing religious values ​​through the Faithful Friday culture is one of the strategies for strengthening the character of students. This research aims to analyze the religious values ​​internalized in the Faithful Friday culture as an effort to strengthen the character of students at Jalaluddin Vocational School, Wonosobo. This research uses a qualitative descriptive research method. Data was obtained through interviews with school principals, Islamic Religious Education teachers and students at Jalaluddin Wonosobo Vocational School. Data analysis techniques use triangulation of sources and methods. The results of this research show that the Faithful Friday culture contains faith values, worship values, wisdom values ​​which can be internalized by students as an effort to form and improve various characters including caring for the environment, love of peace, leadership and responsibility.